2021
DOI: 10.1038/s41598-020-80357-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of trehalase activity by multi-site phosphorylation and 14-3-3 interaction

Abstract: Protein phosphorylation enables a rapid adjustment of cellular activities to diverse intracellular and environmental stimuli. Many phosphoproteins are targeted on more than one site, which allows the integration of multiple signals and the implementation of complex responses. However, the hierarchy and interplay between multiple phospho-sites are often unknown. Here, we study multi‐site phosphorylation using the yeast trehalase Nth1 and its activator, the 14-3-3 protein Bmh1, as a model. Nth1 is known to be ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Qualitatively, we observed that the sequence logo of Max F87 resembles two overlapping PKA motifs. A recent study indicates that PKA is capable of phosphorylating two serines in a row (Dengler et al, 2021). The authors observe in these cases, one serine is constitutively phosphorylated, and the other serine requires increased PKA activity, and hypothesize this multisite phosphorylation might be a regulatory mechanism.…”
Section: Discovery Of Subclasses Of Pka Phosphorylation Consensus Sitesmentioning
confidence: 94%
See 1 more Smart Citation
“…Qualitatively, we observed that the sequence logo of Max F87 resembles two overlapping PKA motifs. A recent study indicates that PKA is capable of phosphorylating two serines in a row (Dengler et al, 2021). The authors observe in these cases, one serine is constitutively phosphorylated, and the other serine requires increased PKA activity, and hypothesize this multisite phosphorylation might be a regulatory mechanism.…”
Section: Discovery Of Subclasses Of Pka Phosphorylation Consensus Sitesmentioning
confidence: 94%
“…In visual exploration of the features learned by reverse homology models, we identified previously unknown features as well. We were interested Max Feature 231 (Figure 5B) that appears to recognize an RRRSS motif that we speculated might represent a basophilic phosphorylation site consensus, perhaps related to two overlapping PKA phosphorylation consensus motifs RRxS [70] [90]. To test this, we analyzed the frequency of two adjacent phosphorylated serines [89] in the 8-amino acid window around the maximally activated position of the top activating sequences and found 2.31 times more doubly phosphorylated regions (13 of 52 IDRs for RRRSSS vs. 15 of 139 IDRs for the feature matching the PKA consensus.…”
Section: Feature Discovery Using Reverse Homologymentioning
confidence: 99%
“…In visual exploration of the features learned by reverse homology models, we identified previously unknown features as well. We were interested Max Feature 231 ( Fig 5B ) that appears to recognize an RRRSS motif that we speculated might represent a basophilic phosphorylation site consensus, perhaps related to two overlapping PKA phosphorylation consensus motifs RRxS [ 70 ] [ 90 ]. To test this, we analyzed the frequency of two adjacent phosphorylated serines [ 89 ] in the 8-amino acid window around the maximally activated position of the top activating sequences and found 2.31 times more doubly phosphorylated regions (13 of 52 IDRs for RRRSSS vs. 15 of 139 IDRs for the feature matching the PKA consensus.…”
Section: Resultsmentioning
confidence: 99%
“…Four residues phosphorylated by protein kinase A (PKA) within the disordered N-terminal fragment of Nth1 have been identified [70]. Site-directed mutagenesis indicated that S83 acts as a high-affinity gatekeeper site to bind Bamh1 (the yeast 14-3-3 isoforms), and S60 acts as a second site to bind to the Bmh1 dimer and activate Nth1 [71]. In addition, PKA sites S20 and S21 regulate the dephosphorylation of Nth1 at the downstream Bmh1 site.…”
Section: Gh37 Trehalasementioning
confidence: 99%